2016
DOI: 10.1080/13102818.2016.1172510
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine levels in a Ramadan fasting model in rats: a case control study

Abstract: Eating habits as well as physical exercise are very important for a healthy lifespan. Ramadan-type fasting, which is food and water avoidance during the daylight period for four weeks, has drawn attention due to its positive impacts on metabolism and health. The aim of this study was to compare the blood and urine catecholamine (CA) levels in fasting and non-fasting rats, in terms of stress response. A total of 20 male rats were randomly divided into a fasting group and a control group. Four weeks later, blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, interestingly, based on the available evidence shows that the use of HFHF has a synergistic effect in inducing metabolic syndrome in experimental animals [5]. In addition, rats are nocturnal animals that are more suitable for fasting to be carried out at night [5], [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, interestingly, based on the available evidence shows that the use of HFHF has a synergistic effect in inducing metabolic syndrome in experimental animals [5]. In addition, rats are nocturnal animals that are more suitable for fasting to be carried out at night [5], [21].…”
Section: Discussionmentioning
confidence: 99%
“…Food and water availability are important factors that determine the species survival. It has been suggested that prolonged fasting and hydric restriction produce changes in the synthesis and liberation of catecholamines (Landsberg, 2006;Bucaktepe et al, 2016). Catecholamines play a major role in the adaptation to low temperatures through non-shivering thermogenesis, which involves the regulation of blood flow, heart rate and an increment of the basal metabolism of highly calorigenic tissues like brown addipose tissue and muscles (Janský, 1963;Rowland et al, 2015).…”
Section: Discussionmentioning
confidence: 99%